Association of Intraoperative Blood Transfusions on Postoperative Complications, 30-Day Readmission Rates, and 1-Year Patient-Reported Outcomes. Issue 8 (15th April 2017) - Elsamadicy, Aladine A.; Adogwa, Owoicho; Vuong, Victoria D.; Mehta, Ankit I.; Vasquez, Raul A.; Cheng, Joseph; Bagley, Carlos A.; Karikari, Isaac O.
Abstract : Study Design: Ambispective cohort review. Objective: The aim of this study was to determine the effect of allogeneic red blood cell (RBC) transfusion on postoperative patient complications profiles and 30-day readmission rates following elective spine surgery. Summary of Background Data: Thirty-day hospital readmission rates are being used as a proxy for quality of care. Intra- or perioperative allogeneic RBC transfusions are associated with deleterious effects. Whether allogeneic RBC transfusions are associated with higher perioperative complications and 30-day readmission rates after elective spine surgery remains unknown. Methods: The medical records of 160 patients undergoing elective spine surgery at a major academic medical center were reviewed. Patient demographics, comorbidities, and postoperative complication rates were collected. All patients completed patient-reported outcomes instruments (Oswestry Disability Index, SF-36, and VAS-NP/BP/LP) before surgery, then at 3, 6, and 12 months after surgery. The association between intra- or perioperative allogeneic RBC transfusions and 30-day readmission rate was assessed via multivariate logistic regression analysis. Results: Baseline characteristics were similar in both cohorts. The mean pre- and postoperative hemoglobin levels were lower for the transfusion than nontransfusion cohorts. Postoperative complication rates were 44.67% and 23.00% in the transfusion and nontransfusion cohorts, respectively. Overall, 9.38% of patients were re-admitted within 30 days of hospital discharge, with a three-fold higher increase in 30-day readmission rate in the transfusion cohort compared to the nontransfusion cohort (no transfusion: 5% vs. transfusion: 16.67%, P  = 0.01). In a multivariate logistic regression model, intra- or perioperative allogeneic RBC transfusion was an independent predictor of 30-day readmission after elective spine surgery ( P  = 0.005). Conclusion: Our study suggests that allogeneic RBC transfusions may be associated with increased postoperative complications, length of hospital stay, and 30-day readmission rates. Level of Evidence: 3